Torrefaction of insecticide treated bed net waste combined with biomass residue to produce high calorific value fuel pellets - Montebon, Chito C. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Torrefaction is a thermal treatment of biomass to enhance its energy density which can be comparable to coal. Waste insecticide treated bed nets (ITB) waste is used as a feed to the process to convert to auseful solid fuel pellets. This bed net contains a long lasting insecticide called permethrin which can kill beneficial insects such as spiders, butterflies, bees, etc. including aquatic lives such as fishes and shells when it gets in contact with the bed net. Through torrefaction, it will create a new way to utilize waste of insecticide treated bed nets to a useful fuel. This study is conducted with the use of a batch torrefaction reactor with the feed being combined with acacia leaves as biomass residue. Operating parameters such as temperature (260˚C-300˚C), holding time (15 min-45 min) and ITB ratio to biomass (20%-80%) are being varied independently to determine which parameter significantly affects the energy density of the final product and to choose best operating parameter which can produce energy rich solid fuel. It is being found through factorial design that the ratio of ITB to biomass affects greatly in the energy density of the final product. ITB alone as feed is not suitable for torrefaction due to melting problem inside the reactor, but when combined with a biomass residue, this problem has lessened effectively. Operating parameters such as 20% ITB, 45 minutes holding time and 300˚C are found to produce high energy density solid fuel. The torrefied ITB with leaves are then being compacted and formed as pellets to simplify material handling and storage.
Thesis (M.S. Energy Engineering)--University of the Philippines, Diliman
Keywords: Wood pellets; Mosquito nets